Promoting a more empowering motivational climate in physical education: a mixed-methods study on the impact of a theory-based professional development programme - Daniel Milton; Paul R. Appleton; Anna Bryant; Joan L. Duda (Frontiers in Psychology, 2025)
This study examined the effects of the delivery of a school-tailored Empowering PE™ workshop and subsequent Professional Development Programme (PDP) using Community of Practice principles within one secondary school Physical Education (PE) department. Employing a mixed-methods longitudinal design, the research assessed PE teachers' understanding of motivation and motivational strategies, Senior Leadership Team perceptions of the PDP's impact, and pupils' motivation and engagement in PE. The intervention pulled from Achievement Goal Theory and Self-Determination Theory, adopting Duda's theoretically integrated conceptualization of empowering and disempowering motivational climates. Qualitative data from interviews, focus groups, and reflections revealed significant perceived benefits for teachers' understanding and implementation of motivational strategies, as well as perceived improvements in pupil engagement and motivation. Quantitative data (147 Year 9 pupils aged 13–14 years, M = 13.6, SD = 0.4; 81 boys, 64 girls) revealed no significant differences over time in perceptions of the motivational climate and their motivation to engage in PE. Overall, this study contributes to the growing body of evidence supporting the benefits of creating empowering environments in physical education. The findings however highlight the complexity of implementing and assessing the effects of motivational climate interventions in PE settings and underscore the importance of sustained, theory-informed professional development for teachers. Areas for future research on interventions (and testing their effectiveness) to optimize the motivation climate in PE, pupil motivation and teacher professional development are provided.